An Analysis of Utilization Differences for Scientific and Technical Information - Gerstenfeld, Arthur; Berger, Paul (Management Science, 1980)
The purpose of this paper is to provide further insight into the process of scientific and technical information transfer. We present and analyze results of data gathered over a two year period from more than 300 engineers and scientists employed at five major U.S. corporations (Xerox, Hewlett-Packard, Monsanto, Exxon, and G. D. Searle). We consider a variety of factors along the axes of “task to be performed” and “information characteristics” and analyze differences in the use of information as a function of these factors. Many interesting results emerge, with important managerial implications. We found that useful information transfer occurs most often toward the start of applied research projects and toward the end of basic research projects. Information supplied late in the project to the applied researcher is of little or no value. There is a “window” for information and this differs among applied and basic researchers. Information repositories, such as traditional corporate libraries with slow turn-around time might be appropriate for basic researchers, but might just as well be nonexistent for many applied researchers. The reasoning is that at the outset of a basic research project, the scientist is acquiring some information, but he is often spending a large portion of his time formulating the problem. As the problem gets better defined, he then seeks additional information to assist his understanding of the (now) better defined problem, or to improve die solution to the problem. His information seeking therefore increases over time. On the other hand, the applied researcher often has a clearer and more defined problem to begin with. He is in a position to immediately seek and acquire (and benefit from) information. Toward the end of the applied research project, the researcher is faced with a severe time limitation and can often accept no further information even though it might have been extremely pertinent if acquired earlier. We found that information sources are relatively more likely to be written for basic research projects, and to be oral for applied research projects, confirming earlier studies. For applied and development projects, easy access to colleagues for face-to-face communication is vital. The linkage by the applied group beyond the immediate project team is often crucial. Basic research projects often require information from colleagues who are working at locations far away, perhaps in another country. Obviously in these cases, oral communication is relegated to occasional national or international meetings or telephone discussions. The basic researcher often wants to reap the benefits of the peer review system (both the reader and the writer) and is more willing to stand the time delay for the written information source. It was only recently that it was recognized that research and development could indeed be managed at all, and now we are realizing that management must organize differently along the R&D continuum. Basic research information exchange often takes place beyond the organization through preprints and conference proceedings. The applied researcher, on the other hand, should be encouraged to participate in technical seminars within the organization, although often beyond his immediate project team.